Masonry infill walls under blast loading using confined underwater blast wave generators (WBWG) - Pereira, João Miguel (2015)
The vulnerability of the masonry envelop under blast loading is considered critical due to the risk of loss of lives. The behaviour of masonry infill walls subjected to dynamic out-of-plane loading was experimentally investigated in this work. Using confined underwater blast wave generators (WBWG), applying the extremely high rate conversion of the explosive detonation energy into the kinetic energy of a thick water confinement, allowed a surface area distribution avoiding also the generation of high velocity fragments and reducing atmospheric sound wave. In the present study, water plastic containers, having in its centre a detonator inside a cylindrical explosive charge, were used in unreinforced masonry infills panels with 1.7m by 3.5m. Besides the usage of pressure and displacement transducers, pictures with high-speed video cameras were recorded to enable processing of the deflections and identification of failure modes. Additional numerical studies were performed in both unreinforced and reinforced walls. Bed joint reinforcement and grid reinforcement were used to strengthen the infill walls, and the results are presented and compared, allowing to obtain pressure-impulse diagrams for design of masonry infill walls.